Trans-oral, Carbon Dioxide-Assisted Excision of an Unusual Schwannoma of the Tongue Base: Case Report and Review of the Literature - Soliman, Zakaria Raee; Mobashir, Mohammad Kamal; Askar, Sherif Mohammad (International Archives of Otorhinolaryngology, 2019)
Introduction Schwannomas are benign, solitary, encapsulated tumors that may originate at any site of the peripheral nervous system, with the exception of the olfactory and optic nerves. Schwannomas of the base of tongue are very rare, and only sporadic cases are documented. The tongue base represents a challenge for surgeons. Carbon dioxide (CO2) laser might provide an effective surgical option for such lesions because of the easy access to the lesion, the bloodless surgical field and optimum epithelization of wounds.Objective We present an unusual case of pedunculated schwannoma of the tongue base treated via transoral CO2-assisted excision. We also provide a review of the available literature, in English language, on humans.Data synthesis The authors searched the PubMed database and Google up to July 2018. The following search terms were applied: tongue and lingual, combined with schwannoma and neurilemmoma. Titles and abstracts were screened, and, then, only supraglottic (hypopharyngeal) tongue base masses were considered. Fourteen articles were included in this review, reporting 17 cases. The age of the patients ranged from 9 to 39 years, affecting predominantly females. Dysphagia and lump sensations were the most common presenting symptoms, and the mean follow-up period range was 1.5 to 60 months (mean = 13 months). There was no evidence of recurrence in any of the cases.Conclusion We could conclude that tongue base schwannomas are rare. Transoral complete excision of the tumor is the treatment of choice. CO2 laser surgery is a minimally invasive treatment option that has been performed in few reports with no recurrence and with favorable outcomes.
Keywords: carbon dioxide laser; tongue base schwannoma; deglutition disorders; deglutition